Reversible photo-regulation on the folding/unfolding of telomere G-quadruplexes with solid-state nanopores. Issue 2 (18th November 2020) - Tang, Jing; Wu, Ji; Zhu, Rui; Wang, Zhong; Zhao, Chuanqi; Tang, Peng; Xie, Wanyi; Wang, Deqiang; Liang, Liyuan
Abstract : Reversible photo-regulation on the folding/unfolding of the telomere G4 by SSN. Abstract : The formation of G-quadruplexes (G4) in human telomere and other important biological regions inhibits the replication and transcription of DNA, thereby influencing further cell proliferation. The investigation of G4 formation and unfolding is vital for understanding their modulation in biological processes and life science. Photo regulation is a facile and sensitive approach for monitoring the structures of biomacromolecules and material surface properties. The nanopore-based technique is also prevalent for label-free single-molecule characterization with high accuracy. This study provides a combination of solid-state nanopore technology with light-switch as a platform for the modulation of human telomere G4 formation and splitting under switchable light exposure. The introduction of molecular switch, namely azobenzene moiety at different positions of the DNA sequence influences the formation and stability of G4. Three azobenzenes immobilized on each of the G-quartet plane (hTelo-3azo-p) or four azobenzenes on the same plane (hTelo-4azo-4p) of the human telomere G4 sequence realized the reversible control of G4 folding/unfolding at the temporal scale upon photo regulation, and the formation and splitting of G4 with hTelo-4azo-4p is slower and not thorough compared to that with hTelo-3azo-p due to the coplanar steric hindrance. Moreover, the G4 formation recorded with the combined nanopore and photo-responsive approach was also characterized with fluorescence, and the variation in the fluorescence intensity of the NMM and G4 complex exhibited a different tendency under reverse light irradiation due to the distinct interactions of NMM with the azobenzene-modified G4. Our study demonstrated a controllable and sensitive way for the manipulation of G4 structures, which will be inspiring for the intervention of G4-related cell senescence, cancer diagnosis and drug exploration.